Blocking layer for prevention of current leakage for reversible solid oxide fuel cells and electrolysis cells with ceria-based electrolyte. (16th February 2017) - Sumi, Hirofumi; Suda, Eisaku; Mori, Masashi
Abstract: Doped ceria is one of the most promising materials for an electrolyte of solid oxide fuel cells (SOFCs) and electrolysis cells (SOECs), because it has higher ionic conductivity than stabilized zirconia. However, current leakage through the ceria-based electrolyte occurs in SOFC and SOEC operating conditions, because electron conductivity appears at low oxygen partial pressures. In order to prevent the current leakage, the BaCe0.8 Y0.2 O3− δ (BCY) blocking layer was inserted between Ce0.9 Gd0.1 O1.95 electrolyte (GDC) and Ni-GDC fuel electrode. The open circuit voltage for the cell with BCY blocking layer increased by 50–60 mV compared to that without BCY, suggesting that BCY is a proton-O 2− ion mixed conductor and it has low electronic conductivity. The performance of SOFC and SOEC using the GDC electrolyte and the BCY blocking layer was better than that using a conventional yttria-stabilized zirconia electrolyte at 500 °C. The hydrogen consumption and production was successfully demonstrated in accordance with Faraday's law for the reversible SOFC–SOEC with the GDC electrolyte and BCY blocking layer. Highlights: Y-doped ceria (YDC) has high sinterability than Gd-doped ceria (GDC). Y-doped barium cerate (BCY) can prevent the current leakage through ceria-based electrolyte. Solid oxide fuel cell and electrolyser with GDC and BCY obeys Faraday's law.